DIVERSIFICATION OF THE NIGERIAN ECONOMY THROUGH TOURISM: THE ROLE OF ICT IN EXPLORING TOURISM POTENTIALS IN RURAL AREAS - Okon, Emmanuel O.; Agbogun, Joshua B.; Yusuf, Momoh S. (IJRDO - Journal of Business Management, 2017)
Tourism has become one of the most significant export sectors in many developing countries. A general consensus has emerged that it does not only increases foreign exchange income, but also creates employment opportunities, stimulates the growth of the tourism industry and by virtue of this, trigger overall economic growth. As such, tourism development has become an important target for most governments, especially for development countries. Nigeria is among the richly endowed potential tourist destinations in the world. Its tourism attractions are abundantly available especially in the rural areas and they are untapped. However, the accelerating and synergistic interaction between technology and tourism in recent times has brought fundamental changes in the industry and the perceptions of its nature. To explore the potential of rural tourism and have the tourism sector of Nigeria contribute maximally to the national economy as a major export earner like petroleum, this paper suggests local content development in the area of information and communications technology (ICT). This is after the paper had examined the Global Tourism Industry; Rural Tourism Potentials in Nigeria; the state of ICT in Nigeria